The Effects of Utilizing a Questioning Development Activity Package to Enhance Logical Thinking Skills for Science and Technology Subject Teachers - Kraimak, Suwat; Kraimak, Sakaorat (An Online Journal of Education, 2026)
This research aimed to 1) develop a teacher questioning development activity package to enhance logical thinking skills for teachers of science and technology learning subjects, and 2) study the effects of using the activity package. The sample consisted of 10 primary teachers teaching in the Science and Technology in grade 6 at a school under the office of Phayao primary educational service area office 2. They were selected by purposive sampling. The research instruments were a questioning activity assessment form, test, a questioning ability assessment form, and a satisfaction assessment form. Statistics used in data analysis included mean (M), standard deviation (SD), and relative growth values. The research results found that 1) the teacher questioning development activity package to enhance logical thinking skills was highly appropriate. The package consisted of six activities: (1) questioning to create a safe learning space (2) understanding levels of questions (3) questioning to stimulate independent thinking (4) practicing question design based on situations (5) practicing question design in lesson plans, and (6) blended supervision processes, and 2) The development outcomes showed that the teachers’ knowledge and understanding of questioning to enhance logical thinking skills were at the highest level. The evaluation of teachers’ ability to design and utilize questions to enhance logical thinking skills in the three areas: (1) designing questions in lesson plan (2) process of using questions to enhance logical thinking, and (3) result of using questions to enhance logical thinking with learners were all at the highest level. And teachers’ satisfaction with the development of questioning to enhance teacher’s logical thinking skills was also at the highest level.